Moderating Role of Social Support on the Relationship Between Job Demand and Presenteeism - Shimabuku, Rose Helen; Mendonça, Helenides (Paidéia (Ribeirão Preto), 2018)
The pressures of contemporaneity and the increase of unemployment cause employees to attend work when sick, becoming presenteeist. The purpose of this study was to investigate the influence of psychological demands on presenteeism, considering the support of the bosses and the control of work as moderators of this relationship. A quantitative cross-sectional study was developed at a Public Institution of Higher Education. 204 technical-administrative servants who responded to the Stanford Presenteeism Scale - SPS6 and the Job Content Questionnaire - JCQ participated in the study. The results indicate that the greater the support of the boss and the control that the employee has of his/her work the less the presenteeism, even in the face of high psychological demands of the work. This study contributes to the investigation of organizational antecedents (demands of work and social support) and personal (control) of presenteeism.